Intra‐individual dynamics of lesson‐specific engagement: Lagged and cross‐lagged effects from one lesson to the next. (25th December 2020) - Vasalampi, Kati; Muotka, Joona; Malmberg, Lars‐Erik; Aunola, Kaisa; Lerkkanen, Marja‐Kristiina
Abstract : Background: Student engagement denotes active participation in academic work through commitment and involvement in learning tasks (Appleton et al., 2006, Journal of School Psychology, 44, 427). This study looks at questions such as whether engagement experiences in one lesson have an effect on the next lesson. In the present study, process‐oriented analyses were conducted to examine lower secondary school students' engagement experiences and the stability of those experiences from one lesson to the next. Aims: (1) To what extent are students' engagement experiences, in terms of behavioural and cognitive engagement, emotional engagement, and disaffection, stable from one lesson to the next (autoregressive cyclic effects)? (2) What are the cross‐lagged relationships (dynamic effects) between engagement experiences from one lesson to the next? Sample: The sample consisted of 56 Finnish lower secondary school students. The students provided ratings of their engagement experiences at the end of each lesson for one week (5 days, 975 ratings). Each student rated, on average, 17.4 lessons ( SD = 5.67). Methods: We specified multilevel dynamic structural equation models with random slopes. Results: The models showed small significant sustainability in behavioural and cognitive engagement, emotional engagement, and disaffection from one lesson to the next, regardless of subject matter and teacher continuity. Higher behavioural and cognitive engagement in a lesson also had a self‐diminishing effect on disaffection. Conclusions: The present study provides valuable information to teachers by showing that an experience in one lesson can have an effect on subsequent ones.